Understanding the Greenium between Green and Conventional Bonds: A Simulation Study - Traore, Abdelmoumine (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper examines the pricing disparity between green and conventional bonds (the greenium), drawing on empirical research findings that have yielded mixed re- sults. We introduce a mathematical model to elucidate the conditions under which green bonds may be priced differently from their conventional counterparts. Un- like previous studies primarily focused on firm-level characteristics, our model incor- porates investors’ prosocial attitudes, income levels, and risk preferences to derive market prices for green bonds. By considering both supply and demand dynamics, we pioneer an equilibrium-based approach to pricing, departing from the assump- tions of traditional models like CAPM and Black-Scholes. Additionally, we integrate regulatory risk into our analysis, introducing the concept of ”green default” along- side pecuniary default. Our findings underscore the influence of investors’ prosocial preferences, issuer environmental commitments, and issuance costs on the greenium. Moreover, stringent environmental policies and advancements in green technology mitigate the likelihood of green default, thereby bolstering market demand for green bonds. While climate risk exerts downward pressure on bond prices overall, its im- pact on the greenium varies based on the relative reduction in the equilibrium price of green bonds compared to conventional bonds.